Droplet spectrum of a spray nozzle under different weather conditions (Revista Ciência Agronômica, 2018)
The application of pesticides is always susceptible to losses through evaporation and drift of the spraydroplets. With these losses, a smaller amount of pesticide reaches the target, possibly impairing the efficiency of phytosanitarycontrol. Due to these concerns, the aim of this study was to evaluate the interference of weather conditions in the dropletspectrum produced by hydraulic spraying. To carry out the work, it was necessary to build an experimental system. Thisconsisted of a laser particle-size analyser, hydraulic nozzle (Jacto JSF 11002), stationary sprayer, gas heater, wind tunnel,climate chamber (with the aim of maintaining the internal psychrometry similar to that of the air exiting the wind tunnel),collector, and temperature and RH sensors. The weather conditions for the study included vapour pressure deficits (VPD)of 5, 9.4, 20, 30.6 and 35 hPa, and air velocities of 2, 3.6, 7.4, 11.2 and 12.8 km h-1. A Rotatable Central Composite Designwas used, and the data related using Response Surface Methodology. The wind caused such a sharp drift in the fine droplets,that it greatly affected the behaviour of the entire droplet spectrum, as well as hiding the effect of the VPD. However, theconclusion is that drift and evaporation both act on the coarser droplets.